Study of structural-mechanical characteristics of emulsion-foam systems of milk cream and hydrocoloids - Kambulova, Yuliia; Zviahintseva-Semenets, Yuliia; Shevchenko, Anastasiia; Kokhan, Olena (My University, 2020)
The present study investigates the emulsion-foam structures of the cream from churned cream with a 20% fat content used in decorating flour confectionery. It is proposed to stabilise such systems by the introduction of sodium alginate, ι-carrageenan or gelatin. It was determined that the emulsion-foam structures of the cream samples under investigation belong to the class of pseudoplastic non-Newtonian fluids. Total deformation, lastic deformation and springy deformation were also investigated.
Keywords: emulsion-foam systems; milk cream; hydrocolloids; springy-plastic properties; rheological properties; кафедра технології хлібопекарських і кондитерських виробів